Acerola Fruit as a Possible Antimelanotic Agent in White Shrimp (Litopenaeus vannamei). (25th November 2015) - Gonçalves, Alex Augusto; Oliveira, Adriene Rosceli Menezes de; Abrantes, Maria Rociene
Abstract : This study aimed to testify acerola's inhibitory activity on melanosis in farmed white shrimp ( L. vannamei ). Shrimp samples underwent immersion in different treatments (control group (C), metabisulphite solution group (M), and acerola solution group (A)). Quality Index Method (QIM) was used to measure the shrimp shelf life, during 21 days, where microbiological, chemical, and sensory analyses were performed at each 3 days. Groups C and A exceeded the limit of mesophilic bacterial count within 15 days of storage, and for M the period was 18 days. As for the psychrophilic bacteria, C and A both crossed the limit on day 12 and M on the 15th day. Group M had the highest TVBN and pH means, followed by A and lastly C. Yet, TMA analysis showed highest values in group C, second A, and finally M. Sensory analysis determined the shelf life of groups C, M, and A as 10.5, 14.6, and 12.3 days, respectively. There were not many significant differences between the groups in all analyses; hence, dipping shrimp in acerola solutions would not suffice to inhibit melanosis formation. Further studies are needed to fully determine acerola's antimelanosic potential.